1999
DOI: 10.1007/s001980050259
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Risk Factor Patterns Between Cervical and Trochanteric Hip Fractures

Abstract: The two types of hip fracture--cervical and trochanteric femoral fractures--are generally considered together in etiologic studies. However, women with a trochanteric fracture may be more osteoporotic than those with cervical hip fractures, and have higher post-fracture mortality. To explore differences in risk factor patterns between the two types of hip fracture we used data from a large population-based case-control study in Swedish women, 50-81 years of age. Data were collected by questionnaire, to which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 39 publications
1
32
3
1
Order By: Relevance
“…In modern epidemiological studies, intracapsular fractures are generally more common than extracapsular fractures (Kannus et al, 1996;Michaëlsson et al, 1999;Zhang et al, 2000), but not always (Maghraoui et al, 2005). These two types of hip fracture are usually considered together in aetiological studies (Michaëlsson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In modern epidemiological studies, intracapsular fractures are generally more common than extracapsular fractures (Kannus et al, 1996;Michaëlsson et al, 1999;Zhang et al, 2000), but not always (Maghraoui et al, 2005). These two types of hip fracture are usually considered together in aetiological studies (Michaëlsson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters also effectively predicted IT and FN fractures after correction for demographic parameters and BMDs. While a number of studies have evaluated hip fractures as a homogeneous condition, IT and FN fractures are two distinct entities that have different risk factors, treatments, and prognoses [3][4][5][6]. In our study, this point was addressed by separate analysis of the data in each type of hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…These two fractures are distinct entities and subject to different surgical treatment. Furthermore, the two fracture types differ in etiology, risk factors, and patient characteristics [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the magnitude of the association between frailty and increased risk of hip fracture appeared slightly greater for trochanteric hip fractures than for femoral neck fractures. Previous studies comparing differences in risk factor patterns between femoral neck and trochanteric fractures (22)(23)(24) have consistently reported that women with trochanteric fractures are more likely to be older and have poorer health status and lower bone density.…”
Section: Discussionmentioning
confidence: 99%